2014
DOI: 10.1186/1475-2875-13-68
|View full text |Cite
|
Sign up to set email alerts
|

First case of a naturally acquired human infection with Plasmodium cynomolgi

Abstract: Since 1960, a total of seven species of monkey malaria have been reported as transmissible to man by mosquito bite: Plasmodium cynomolgi, Plasmodium brasilianum, Plasmodium eylesi, Plasmodium knowlesi, Plasmodium inui, Plasmodium schwetzi and Plasmodium simium. With the exception of P. knowlesi, none of the other species has been found to infect humans in nature. In this report, it is described the first known case of a naturally acquired P. cynomolgi malaria in humans.The patient was a 39-year-old woman from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

6
249
0
12

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 271 publications
(286 citation statements)
references
References 31 publications
6
249
0
12
Order By: Relevance
“…(C) Inhibition of P cynomolgi countries. [19][20][21] By contrast, to date, only 1 case of zoonotic P cynomolgi has been reported recently from Malaysia, 22 and it came to light solely through careful molecular analysis. Three interrelated factors might account for the disparity in the observed prevalence of zoonotic infections for these 2 species that have similar high prevalence in their natural hosts.…”
Section: Introductionmentioning
confidence: 99%
“…(C) Inhibition of P cynomolgi countries. [19][20][21] By contrast, to date, only 1 case of zoonotic P cynomolgi has been reported recently from Malaysia, 22 and it came to light solely through careful molecular analysis. Three interrelated factors might account for the disparity in the observed prevalence of zoonotic infections for these 2 species that have similar high prevalence in their natural hosts.…”
Section: Introductionmentioning
confidence: 99%
“…4 This parasite is transmitted to humans by the bite of the Anopheles mosquito. Once inside the organism, the parasite causes clinical symptoms that can range from mild to grave, or even lead to fatal.…”
Section: Introductionmentioning
confidence: 99%
“…In 2014, the sixth malarial species, P. cynomolgi, was identified in Southeast Asia, with a single case reported in Malaysia (3). Malaria caused by P. cynomolgi is very difficult to differentiate from that caused by P. vivax (3). In 2015, Lalremruata et al (4) reported the seventh human malarial species, P. brasilianum, this time in South America.…”
mentioning
confidence: 99%
“…Based on 18S rRNA gene sequencing, Lalremruata et al (4) identified 12 patients harboring malaria parasites, which were 100% identical to those of P. brasilianum isolated from the monkey Alouatta seniculus. Indeed, P. brasilianum malaria is important monkey malaria, and the chance for human cross-species infection had already been highlighted (3). Of interest, other carriers of malaria, such as the monkeys P. eylesi, P. inui, P. schwetzi, and P. simium, provide an opportunity for cross-species infection.…”
mentioning
confidence: 99%